Performa Ayam Arab dengan Pemberian Energi-Protein pada Level Berbeda - Windawati Alwi; Laily Agustina; Muhammad Zain Mide (Universitas Sulawesi Barat, 2019)
This research aimed to determine the effect of different energy and protein level giving in Arabic chicken on feed consumption, egg production and feed conversion. The materials used for this experiment were 80 heads of arabic chicken 5 months age and maintained for 6 weeks (36 days). The method used was completely randomized design (CRD) which consists of 4 treatments and 10 replications that R1 (protein 15% and EM 2 500 Kcal), R2 (protein 16% and EM 2 600 Kcal), R3 (protein 17% and EM 2 700 Kcal) and R4 (protein 18% and EM 2 800 Kcal). Analysis of variance showed that treatment significantly (P<0.05) on feed consumption, egg production and feed conversion. It could be concluded that more increasing energy and protein, the higher egg production, feed consumption and generates optimal feed conversion. Energy and protein with a protein level of 18% and energy 2 800 Kcal kg-1 showed better performance.